Historicising gender and sexuality - Murphy, Kevin P., 1963-; Spear, Jennifer M., 1967- (Malden, MA : Wiley-Blackwell, 2011)
'Historicising Gender and Sexuality features a diverse collection of essays that shed new light on the historical intersections between gender and sexuality across time and space. Features a wide and diverse range of scholarship to explore the historical intersections between gender and sexuality across space and time Demonstrates both the particularities of specific formulations of gender and sexuality and the nature of the relationship between the categories themselves Presents evidence that careful and contextualised analysis of the shifting relationship of gender and sexuality illuminates broader historical processes'--
'Gender and sexuality are inextricable components of the human experience that remain as complex today as throughout world history. Historicising Gender and Sexuality features a thought-provoking collection of essays that shed important new light on the historical intersections between gender and sexuality across time and space. Several of the authors conclude that the constructions, practices, and experiences of gender and sexuality are far more entangled and mutually constitutive than previous scholarship has suggested. A wide swath of topics in various historical contexts are explored - from sexual activities in sixteenth-century New Spain to contemporary Miami; from attitudes revealed in Chinese sexology to American nudist magazines; and from the experiences of free women of colour in the British Caribbean to ideas put forth by 20th-century Egyptian reformers. Essays demonstrate the particularities not just of specific formulations of gender and sexuality in different historical contexts, but of the very nature of the relationship between the categories themselves. Through a rich diversity of scholarship, the essays offer ample evidence that careful and contextualised analysis of the shifting relationship of gender and sexuality illuminates broader historical processes. This book offers revealing insights into the myriad ways in which gender and sexuality have crossed paths with broader relations of power in a wide range of locations and historical contexts'--
'Originally published as Volume 22, Issue 3 of Gender & History.'
Includes bibliographical references and index.
Keywords: Gender identity -- History; Sex -- History